The effect of Northeast Monsoon on the physical—chemical parameters and DFE(III) ions at Pulau Redang, Terengganu - Ramjam, Nur Jannati; Mohamed, Khairul Nizam; Amiruddin, Muhaimin (Universiti Malaysia Terengganu, 2025)
The physical-chemical parameters and dissolved Fe(III) ion distribution [dFe(III)] were determined throughout the water column at Pulau Redang, Terengganu. This study was carried out in March 2019 and October 2019 to evaluate the possible effect of the Northeast Monsoon (NEM) on the pH, salinity, dissolved oxygen, turbidity, conductivity, and dFe(III) ion concentration. The determination of dFe(III) ion was carried out by using the optimised adsorptive-cathodic stripping voltammetry (AdCSV) method. The results show a change in physical and chemical conditions between March 2019 and October 2019 is due to the seasonal NEM phenomenon. However, the dFe(III) ion concentrations did not differ significantly (p > 0.05) in March 2019 and October 2019. This indicates that the NEM does change the physical-chemical condition of the water column and has no effect on the distribution of Fe(III) ions in our study area.